2011
DOI: 10.1080/09658211.2010.494046
|View full text |Cite
|
Sign up to set email alerts
|

SenseCam as a rehabilitation tool in a child with anterograde amnesia

Abstract: We present the case of a 13-year-old boy, CJ, with profound episodic memory difficulties following the diagnosis of a metastatic intracranial germ cell tumour and subsequent treatment with radiotherapy and chemotherapy. At the core of this study is the first application of SenseCam to a child with severe memory impairment. CJ was taken for a walk while he was wearing SenseCam. This included visiting four different locations. We manipulated the number of locations he could review on SenseCam "films" and then te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 28 publications
1
33
0
Order By: Relevance
“…Very longterm recall was also observed (67% at 2 months, 76% at 3 months). In comparison with a personal diary, SenseCam thus enabled sustained long-term recall (results corroborated by [40] in a 63-year-old woman with limbic encephalitis, by [48] in a 28-year-old man with brain trauma, by [49] in a 55-year-old woman with mild cognitive impairment, and by [44] in a 13-year old with anterograde amnesia). SenseCam was also 216 217 218 219 220 221 222 223 224 225 226 227 228 229 230 231 232 233 234 235 236 237 238 239 240 241 242 243 244 245 246 247 248 249 250 251 252 253 254 255 256 257 258 259 260 261 262 263 264 265 266 267 268 269 270 271 272 273 2...…”
Section: Case Studiesmentioning
confidence: 63%
See 3 more Smart Citations
“…Very longterm recall was also observed (67% at 2 months, 76% at 3 months). In comparison with a personal diary, SenseCam thus enabled sustained long-term recall (results corroborated by [40] in a 63-year-old woman with limbic encephalitis, by [48] in a 28-year-old man with brain trauma, by [49] in a 55-year-old woman with mild cognitive impairment, and by [44] in a 13-year old with anterograde amnesia). SenseCam was also 216 217 218 219 220 221 222 223 224 225 226 227 228 229 230 231 232 233 234 235 236 237 238 239 240 241 242 243 244 245 246 247 248 249 250 251 252 253 254 255 256 257 258 259 260 261 262 263 264 265 266 267 268 269 270 271 272 273 2...…”
Section: Case Studiesmentioning
confidence: 63%
“…The study by Loveday and Conway [38] conducted in a 47-year-old woman with a damaged medial temporal lobe also showed increased specificity for events not present in the images, results that support our hypotheses. Elsewhere among the case studies, two studies indicated an improvement in semantic autobiographical memory [44,45]. Pauly-Takacs et al [44] studied a 13-year old with anterograde amnesia due to intracranial metastases and Garood [45] studied a 10-year old with encephalopathic hypoxic ischemia.…”
Section: Case Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Lee and Dey (2008), and then to re-play their day thus triggering short-term recall and re-opening some of their cognitive pathways, albeit briefly. Studies at Addenbrook's hospital in Cambridge, U.K. and elsewhere show measurable effects of improved memory after replay of a given day's activities, though on a small sample size, as described in Berry et al (2009);Pauly-Takacs et al (2011);Silva et al (2013). In ; a memory re-finding use of lifelogging which is called "iRemember" is presented, where audio clips are used as the main information key to navigate memory and once again these exploit the phenomenon of Proustian recall.…”
Section: Memory Assistancementioning
confidence: 99%